2016
DOI: 10.1145/2912125
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between Abstract Art by Artists vs. Children and Animals

Abstract: expressionism is a school of art characterized by nonrepresentational paintings where color, composition, and brush strokes are used to express emotion. These works are often misunderstood by the public who see them as requiring no skill and as images that even a child could have created. However, a recent series of studies has shown that ordinary adults untrained in art or art history, as well as young children, can differentiate paintings by abstract expressionists and superficially similar works by preschoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Shamir et al (53) have shown that computers are able to exceed in accuracy the detection of abstract art created by children versus actual artists. In this study, Shamir et al (53) used their specialized feature extraction algorithm (15,54), however, it may be possible to obtain similar results using the simple UFLK method demonstrated in our paper. Another similar use of the UFLK features could be to detect when an artist decides to change their painting style.…”
Section: Discussionmentioning
confidence: 99%
“…Shamir et al (53) have shown that computers are able to exceed in accuracy the detection of abstract art created by children versus actual artists. In this study, Shamir et al (53) used their specialized feature extraction algorithm (15,54), however, it may be possible to obtain similar results using the simple UFLK method demonstrated in our paper. Another similar use of the UFLK features could be to detect when an artist decides to change their painting style.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the researches carried out results using abstract paintings (Alvarez et al, 2015;Nissel et al, 2015;Shamir et al, 2016;Bubić et al, 2016;Mullennix & Robinet, 2018). Sometimes abstract paintings may be confusing to understand at first quick look, but if done correctly, they also have a profound appeal to them.…”
Section: Art and Titlementioning
confidence: 99%
“…Therefore, differences could be identified not only by adults without any knowledge of art history but also by computers. One of the latest studies (Shamir et al, 2016), the researcher tried to find out if machine perception could distinguish differences between human, child, and animal abstract paintings. They show that the computer algorithm can discriminate between abstract paintings and children's and animal's work in 68 per cent of cases.…”
Section: Art and Titlementioning
confidence: 99%
See 1 more Smart Citation
“…The style matrix is used for image and style retrieval on image database. Shamir et al [17] presented a recognition scheme for abstract expressionism by evaluating the relation between the level of artistic and visual contents. Lecoutre et al [12] employed deep residual network for recognizing artistic style of artwork images in WikiArt database.…”
Section: Classification Of Artistic Stylesmentioning
confidence: 99%